The Review оf the Iranian Magazines оf The Social аnd Humanitarian Orientation (Following the Results of Scientifi c Business Trip). - Nadirova G. Е. (Journal of Oriental Studies, 2016)
This article, written on the basis of scientifi c mission to the Islamic Republic of Iran, is a brief overview of several Iranian journals in social humanities